If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19p + q + -6p + 8q = 0 Reorder the terms: 19p + -6p + q + 8q = 0 Combine like terms: 19p + -6p = 13p 13p + q + 8q = 0 Combine like terms: q + 8q = 9q 13p + 9q = 0 Solving 13p + 9q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9q' to each side of the equation. 13p + 9q + -9q = 0 + -9q Combine like terms: 9q + -9q = 0 13p + 0 = 0 + -9q 13p = 0 + -9q Remove the zero: 13p = -9q Divide each side by '13'. p = -0.6923076923q Simplifying p = -0.6923076923q
| 2/5c-12=-32 | | 1/6[6w-12]=6-2[w-2 | | 8yt+x=3y+9x-5xy | | 49t^2=100 | | 3x+7z=21 | | 4m-[8-m]=6-2m | | 11r=9r | | 4u-7=u+3[4+u] | | 2/3h-4-2/3h-3=2/3h-6 | | (13x)+(11y)=212 | | 2/3h-4_2/3h-3=2/3h-6 | | x-.2x=523 | | 5x-7/x=3 | | 49x^2-126xy+81y=0 | | 6x((7-x)(7-x))=0 | | x^14-36=0 | | 3m-5=5m+8 | | 3m-6=gm+8 | | 18a^2/3a-4 | | 3u/5=18 | | 3xp=9 | | 117/429 | | 3y=15/2 | | 1/6x=29/54 | | 10.24=u/8 | | (x-2)(x-3)=(k-2)(k-3) | | x^12-36=0 | | p=30x^2-220x-10 | | 1/9×3/4 | | f(x)=4-3/4 | | 6x+9=109 | | 3x+5=39 |